Comparison of Inflammatory Markers in the Diagnosis of Metabolic Syndrome in Hemodialysis Patients: A Multicenter Observational Study - Song P; Zhao Y; Zhang H; Chen X; Han P; Fang C; Yu C; Guo Q (Diabetes, Metabolic Syndrome and Obesity, 2022)
Peiyu Song,1 Yinjiao Zhao,1,* Hui Zhang,1,* Xiaoyu Chen,2 Peipei Han,2 Chenghu Fang,1 Chen Yu,3 Qi Guo1,2 1Department of Rehabilitation Medicine, Jiangwan Hospital of Shanghai Hongkou District, Shanghai University of Medicine and Health Science Affiliated First Rehabilitation Hospital, Shanghai, People’s Republic of China; 2Department of Rehabilitation Medicine, Shanghai University of Medicine and Health Sciences, Shanghai, People’s Republic of China; 3Department of Nephrology, Tongji Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qi Guo, Department of Rehabilitation Medicine, Shanghai University of Medicine and Health Sciences Affiliated Zhoupu Hospital, 1500 Zhouyuan Road, Pudong New District, Shanghai, 201318, People’s Republic of China, Tel/Fax +86-22-8333-6977, Email guoqijp@gmail.com Chen Yu, Department of Nephrology, Tongji Hospital, School of Medicine, Tongji University, No. 389 Xincun Road, Shanghai, 200065, People’s Republic of China, Tel +86-13311996821, Email yuchen@tongji.edu.cnObjective: The purpose of this study is to observe the correlation between high sensitivity C-reactive protein (hs-CRP) and metabolic syndrome (MetS) in hemodialysis patients, determine its optimal cut-off point value, and compare the diagnostic ability of different inflammatory markers for MetS.Methods: This cross-sectional study finally included 860 long-term hemodialysis patients (male 524, average age 61.5 years) from seven dialysis centers in Shanghai, China. The International Diabetes Federation metabolic syndrome guidelines were used to define MetS, including high waist circumference, elevated blood pressure, elevated fasting blood glucose, elevated triglycerides, and reduced HDL cholesterol. Serum hs-CRP was determined by the immunonephelometric assay. The association with MetS was observed according to the quartile of inflammatory markers, and then the optimal cut-off point value of the hs-CRP was determined by ROC analysis.Results: The overall prevalence of MetS was 55.1% (46.6% in males and 68.5% in females). In the final logistic regression model, there was a significant, graded positive association between hs-CRP and MetS (p for trend = 0.010). The traditional inflammatory markers leukocytes, neutrophils, lymphocytes, monocytes and neutrophil-to-lymphocyte ratio (NLR) were not associated with MetS. The results of the ROC analysis showed that the optimal cut point value of hs-CRP for the diagnosis of MetS was 1.58 mg/L. In the components of MetS and hs-CRP was significantly positively associated with high waist circumference, elevated TG and low HDL (p < 0.05).Conclusion: The increase in hs-CRP concentration is significantly associated with the risk of MetS, and the diagnostic ability of hs-CRP for MetS is better than traditional inflammatory markers.Keywords: metabolic syndrome, inflammatory markers, high sensitivity C-reactive protein, hemodialysis